ANALISIS KINERJA PEGAWAI BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENANGANAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN BERAU - Djupiansyah Ganie; Isroiyah Isroiyah; Dawami Buchori (Jurnal Ekonomi STIEP, 2021)
The purpose of this research was to identify and clearly describe the performance of the Regional Disaster Management Agency (BPBD) employeesin handling forest and land firesin Berau Regency. The primary data source isin the form of questionnaire data which is distributed to 64 BPBD employees of Berau Regency using saturated sampling method or census. The analytical tools used include: validity and reliability tests, and weighted factor value methods.This study concludes that the results of the respondents' answers to the questionnaire regarding theperformance of BPBD employees in handling forest and land fires show varied answers, be it "very good", "good", "not good", "not good" and "very bad". . Positive responses consisting of answers "very good" and "good" amounted to 81.5% of all respondents' answers. This positive response was much greater than the negative response given by respondents which was only 18.5%, which consisted of the answers "not good" (16.0%), "not good" (2.1%) and "very not. good ”(0.4%).The total value of the weighted factors obtained from the calculations that have been done previously is 4.2.This value is included in the criteria N> 3 (average / mean value), which means that the performance of Regional Disaster Management Agency (BPBD) employees in handling forest and land firesin Berau Regency is good. So it can be concluded to reject the hypothesis in this study, which states that the performance of BPBD employees in handling forest and land fires in Berau Regency is not good.